Perceptions of a good death: A qualitative study in intensive care units in England and Israel. (October 2016) - Endacott, R.; Boyer, C.; Benbenishty, J.; Ben Nunn, M.; Ryan, H.; Chamberlain, W.; Boulanger, C.; Ganz, F.D.
Summary: Objectives: To explore factors perceived to contribute to 'a good death' and the quality of end of life care in two countries with differing legal and cultural contexts. Design and methods: Multi-centre study consisting of focus group and individual interviews with intensive care nurses. Data were analysed using qualitative thematic analysis; emotional content was analysed using specialist linguistic software. Settings/participants: Fifty five Registered Nurses in intensive care units in Israel ( n = 4) and England ( n = 3), purposively sampled across age, ICU experience and seniority. Findings: Four themes and eleven sub-themes were identified that were similar in both countries. Participants identified themes of: (i) timing of communication, (ii) accommodating individual behaviours, (iii) appropriate care environment and (iv) achieving closure, which they perceive prevent, and contribute to, a good death and good quality of end of life care. Emotional content showed significant amount of 'sadness talk' and 'discrepancy talk', using words such as 'could and 'should' when participants were talking about the actions of clinicians. Conclusions: The qualities of a good death were more similar than different across cultures and legal systems. Themes identified by participants may provide a framework for guiding end of life discussions in the intensive care unit.